Intrusäo alcalina de Morro Preto (GO): Geologia, petrografia e geoquímica - Navarro, Guillermo Rafael Beltran [UNESP]; Zanardo, Antenor [UNESP]; da Conceição, Fabiano Tomazini [UNESP]; Angeli, Nélson [UNESP] (My University, 2014)
The alkaline intrusion of Morro Preto, located to the north of Piranhas (GO), Is an irregular to subcircular rock body with about 3,34 km2, hosted in gneisses of the Goiás Magmatic Arc. It is chiefly constituted by carbonatites and lamprophyres with several degrees of laterization and silicification, as well as silexites and minor contents of ferruginous syenites and alkaline basalts. Chemically, it shows low concentrations in Cs, K, Na, Rb and high contents of REE, Nb, Ba, Th and U. This is probably due to the processes of laterization/silicification, and to the new rare mineral phases formed, i.e., phosphates with high concentration in REE and Th, oxi-hydroxides of Fe, Ba and Mn, and/or siliceous phosphates of REE, Nb, Ta, among others, and barite formation. Carbonatitic rocks with high P2O5 and expressive enrichment in REE suggests possible mineralization in these components, similar to other alkaline complexes in Goiás (Catalão) and Minas Gerais (Araxá). The distribution of minor, REE and trace elements show that these rocks are alteration products of alcaline igneous rocks as carbonatites, lamprophyres and alkaline basalts, once these rocks are naturally enriched in elements as Th, U, REE (in special LREE), Nb and Ta. The excessively high contents in these rocks results from supergene enrichment and/or hydrothermal alteration in low temperature.
Alkaline intrusion of black hill (GO): Geology, petrography and geochemistry
Keywords: Alkaline rock; Geochemistry; Morro preto